2010
DOI: 10.1002/ptr.3306
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid‐binding Ability of Kaki‐tannin from Young Fruits of Persimmon (Diospyros kaki) In Vitro and In Vivo

Abstract: The bile acid-binding ability of a highly polymerized tannin (kaki-tannin) extracted from dried-young fruits of persimmon (Diospyros kaki) was examined. The kaki-tannin was composed mainly of epicatechin, epigallocatechin, epicatechin-3-O-gallate and epigallocatechin-3-O-gallate. Bile acid-binding ability of kaki-tannin was examined against cholic acid, glycocholic acid, taurocholic acid and deoxycholic acid in vitro, and its effect on fecal bile acid excretion in mice was also examined. Although the bile acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 10 publications
3
48
0
Order By: Relevance
“…Therefore, young persimmon fruits can act as bile acid-binding agents in vivo. We also found that a highly polymerized tannin (kaki-tannin) is a functional constituent of young persimmon fruits, and demonstrated its beneficial effects against dyslipidemia, including the promotion of fecal bile acid excretion, in mice [11,12]. More recently, crude fiber prepared from young persimmon fruits was found to be responsible for this bile acid-binding property, and the extent of binding was correlated with the condensed tannin content [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, young persimmon fruits can act as bile acid-binding agents in vivo. We also found that a highly polymerized tannin (kaki-tannin) is a functional constituent of young persimmon fruits, and demonstrated its beneficial effects against dyslipidemia, including the promotion of fecal bile acid excretion, in mice [11,12]. More recently, crude fiber prepared from young persimmon fruits was found to be responsible for this bile acid-binding property, and the extent of binding was correlated with the condensed tannin content [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that EGCg can beneficially modify the glucose metabolism of diabetic rodents (23), and that green tea extract can improve plasma cholesterol levels in rodents (24). Highly polymerized tannins in persimmon could be partially hydrolyzed in the presence of HCl solution (6,7), suggesting that the catechins generated from tannins during digestion might play some beneficial role in cholesterol and glucose metabolism.…”
Section: Gene Expression Analysis In the Liver Ewat And Batmentioning
confidence: 98%
“…No sig- nificant changes were observed in the expression of the Shp, Hmgcr, Fas, Gck, or Ucp1 genes. The tannins in persimmon primarily consist of epicatechin, epigallocatechin, epicatechin-3-O-gallate, and epigallocatechin-3-O-gallate (EGCg) (6,7,12), which are reported to be the main polyphenolic components of green tea (22). It has also been reported that EGCg can beneficially modify the glucose metabolism of diabetic rodents (23), and that green tea extract can improve plasma cholesterol levels in rodents (24).…”
Section: Gene Expression Analysis In the Liver Ewat And Batmentioning
confidence: 99%
See 2 more Smart Citations